Concomitant Lumbar Spine Pathology in Patients Undergoing Hip Arthroscopy: A Matched Cohort Analysis. Issue 7 (21st July 2017) - Mahure, Siddharth Ashok; Ryan, Michael K.; Buckland, Aaron; Hamula, Mathew; Begly, John; Capogna, Brian; Looze, Chris; Chenard, Kristofer E.; Wolfson, Theodore; Youm, Thomas
Objectives: Hip arthroscopy for femoroacetabular impingement (FAI) and related hip pathology is increasing in volume. Variable presentations of hip pain often lead to confusion with lumbar spine pathology however. We sought to define the relationship between the lumbar spine and the hip joint. Our hypothesis is that patients with concurrent lumbar spine pathology will experience inferior outcomes after hip arthroscopy when compared to patients without lumbar spine pathology. Methods: Prospectively-collected data from a single-surgeon database from 2010 to 2014 was used to identify patients who had undergone hip arthroscopy and had documented concurrent lumbar spine pathology. Patients with spine pathology were matched by age, gender, and BMI in a 3:1 fashion to patients without spine pathology. Baseline pre-operative modified Harris Hip Scores (mHHS) were compared to scores at two-year follow-up. "Poor outcome" of initial hip arthroscopy was defined as any combination of: requiring a revision procedure, conversion to THA, or mHHS below 70. Results: 167 patients met inclusion criteria: 72.5% were "normal" while 27.5% had spine pathology. Baseline demographics were appropriately matched between cohorts (Table I). Preoperative and two-year mHHS scores were significantly different between cohorts (Figure 1). Both cohorts demonstrated significant within-group improvement at two-year follow-up, however normal patients had greater improvements than those with spine pathology (34.0 vs 31.76, p<0.001). Overall revision/THA conversion rate for entire cohort was 14.97%, with nearly twice as many spine co-pathology patients requiring additional surgery than those in the normal cohort (23.91% vs 11.57%, p=0.045). Patients with spine pathology were significantly more likely to have "poor outcomes" than those without spine pathology (36.96% vs 21.49%, p=0.048). Conclusion: Our results demonstrate that patients undergoing hip arthroscopy with concomitant lumbar spine pathology demonstrate significantly lower total improvement, significantly higher revision/THA conversion rates and significantly higher rates of suboptimal outcomes after hip arthroscopy than patients without spine pathology. Table 1: Baseline Demographic Data Between Cohorts Normal (n=121) Spine pathology (n=46) p value Mean (SD) Age 38.78 (11.38) 42.39 (12.03) P=0.14 BMI 24.03 (3.6) 25.32 (4.9) P=0.13 Gender: present female 62.8% (n=76) 63.1% (n=29) P=0.98 Figure 1: Differences in mHHs scores between Cohorts